All-optical nanoscale thermometry based on silicon-vacancy centers in detonation nanodiamonds. (15th October 2022) - Fujiwara, Masanori; Uchida, Gaku; Ohki, Izuru; Liu, Ming; Tsurui, Akihiko; Yoshikawa, Taro; Nishikawa, Masahiro; Mizuochi, Norikazu
Abstract: Silicon-vacancy (SiV) centers in diamond are a promising candidate for all-optical nanoscale high-sensitivity thermometry because they have sufficient sensitivity to reach the subkelvin precision required for application to biosystems. It is expected that nanodiamonds with SiV centers can be injected into cells to measure the nanoscale local temperatures of biosystems such as organelles. However, the smallest particle size used to demonstrate thermometry using SiV centers is a few hundred nanometers. We recently developed SiV-center-containing nanodiamonds via a detonation process that is suitable for large-scale production. Here, we investigate the spectral response of SiV-center-containing detonation nanodiamonds (SiV-DNDs) to temperature. We used air-oxidized and polyglycerol-coated SiV-DNDs with a mean particle size of around 20 nm, which is the smallest size used to demonstrate thermometry using color centers in nanodiamond. We found that the zero-phonon line for SiV-DND is linearly red-shifted with increasing temperature in the range of 22.0–40.5 °C. The peak sensitivity to temperature was 0.011 ± 0.002 nm/K, which agrees with the reported high sensitivity of SiV centers in bulk diamond. A temperature sensitivity analysis revealed that SiV-DND thermometry can achieve subkelvin precision. All-optical SiV-DND thermometry will be important for investigating nanosystems such as organelles in living cells. Graphical abstract: Image 1